Alfred Werner revisited: Some subtleties of complex ion synthesis and isomerism - Ogden, Mark; Harrowfield, J.; Skelton, B.; White, A. (Elsevier SAS, 2005)
The synthesis of perhaps the best-known Wernerian complex, [Co(en)3]3+, is very efficient, but nonetheless results in the formation of various side-products. Today, the use of X-ray crystallography to characterise such materials provides new insights into the reaction pathways of the synthesis and the exact forms possible for the products. The structures of cis-[Co(en)2(H2NCH2CH2NH3)Cl]Cl[ZnCl4], cis-[Co(en)2(NH3)Cl]S2O6, [Co(en)(NH2CH2CH2N=CHCH2NH2))Cl][ZnCl4], [Co(en)2(N-CH3en)][Co(CN)6]?2 H2O and [Co(en)2(N-CH3en)][Co(CN)6], are presently discussed in this regard.